The era of Social Machines in the BPM-SOA and UML-SOA convergence - Souza, Brunno Wagner Lemos de (2022)
In this work, we have explored and analyzed fundamental concepts of BPM (Business Process Modeling) methodology, as well as software development utilizing UML (Unified Modeling Language), both of which are based on SOA (Service-Oriented Architecture) architecture, as an objective of to integrate the areas of development of software and management of companies as the advent of Social Machines, to enable a more excellent combination of computer and human elements us processes. This study aims to present a possibility of a verified scenario from a survey of the literature that deals with the integration of BPM-SOA and UML-SOA with Social Machines. Thus a comparison was made between the execution languages ​​of both models and the Social Machines to present a possibility of integration between architectures and models. All this ensures interoperability between different entities, adding value and reducing maintenance costs for companies. With the scientific methods that determine the discovery of the problem, observation, pois, constitutes an investigative procedure to understand the possibility of integration and implementation of BPM-SOA and UML-SOA with Social Machines.